Cartografias de um lugar imaginário : uma travessia pelo romance Calunga, de Jorge de Lima. - Almeida, Simone Cavalcante de (2008)
The course of this crossing aims to (re)discover aesthetic and stylistic configurations in Jorge de Lima s novel Calunga, by observing Levitas s (1990) discussions on the three aspects of utopia (form, function and content) as its theoretical cartography. Regarding the issue of form, the analysis proposes that novel signals two ruptures: the dissolution of barriers between genres, having as its basis Cortázar s ideas (1998) and focusing on the identification of a poetic stream acting in narrative the text; and the counterpoint it offers to the form of the traditional utopias, in a self-critical process constructed by the use of symbolic references to the island and the mud. As for the content, two utopian expressions found in the plot, the character Lula s daydream and the saint s mysticism, in approximation to Bloch s (2005) ideas on daydreams and Mannheim s (1982) studies on the chiliastic consciousness, offer the means for an exploration of the utopian phenomenon and its implications. Regarding the utopian function, Moylan s (2003) concept of the critical utopia is used in relation to two articulated movements in the narrative: its self-reflexive quality, in terms of intertextual references to Jorge de Lima s poetry, which compose internal reference paraphrases and is looked at from the perspective of Sant Anna´s (1988) definition of literary paraphrasis; and, considering an outward movent, its relations with canonical narratives of Brazilian premodernist and modernist prose, aiming to stress the convergences between the discourses of utopia, nation and national identity. By choosing the paths in the consolidation of his literary project, Jorge de Lima had his work in prose practically ignored. Finally, the course followed in the present study aims to reposition Calunga in contemporary critical studies.